2018
DOI: 10.1186/s12870-018-1460-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 399 as a potential integrator of photo-response, phosphate homeostasis, and sucrose signaling under long day condition

Abstract: BackgroundPhotoperiod-sensitivity is a critical endogenous regulatory mechanism for plant growth and development under specific environmental conditions, while phosphate and sucrose signaling processes play key roles in cell growth and organ initiation. MicroRNA399 is phosphate-responsive, but, whether it has roles in other metabolic processes remains unknown.ResultsMicroRNA399 was determined to be sucrose-responsive through a microRNA array assay. High levels of sucrose inhibited the accumulation of microRNA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…In addition, the expression level of miR399 can also be affected by sucrose. Previous studies showed that higher endogenous sucrose accumulation was accompanied by higher miR399 expression, whereas exogenous sucrose supplementation inhibited miR399 accumulation under phosphate starvation conditions [53]. In this study, we found the existence of the miR399- NINV module in various plant species (Table 2).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, the expression level of miR399 can also be affected by sucrose. Previous studies showed that higher endogenous sucrose accumulation was accompanied by higher miR399 expression, whereas exogenous sucrose supplementation inhibited miR399 accumulation under phosphate starvation conditions [53]. In this study, we found the existence of the miR399- NINV module in various plant species (Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…Both miR399 and NINVs were found to be sucrose-responsive. External sucrose supplementation inhibits the expression of miR399 in maize [53]. In addition, the NINV expression levels in Poncirus trifoliata were induced by sucrose, and decreaed by glucose [54].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study in maize revealed that the PILNCR1-miR399 regulatory module is important for LP tolerance [47]. Similarly, Tian et al [8] reported that miR399 functions as a potential integrator of phosphate homeostasis. The regulatory protein pho2 results from a nonsense mutation in the target gene of miR399, which can cause excessive phosphate accumulation [50].…”
Section: Putative Functions Of Circrna-mediated Mirna Networkmentioning
confidence: 99%
“…Phosphate starvation also induces miRNA responses in Populus tomentosa [6]. Moreover, as a longdistance signal, miR399 can regulate phosphate homeostasis in plants [7] and can serve as a potential integrator of photoresponses and phosphate homeostasis [8,9]. In Arabidopsis, a new class of small RNAs has been identified in phosphate-starved roots [10], and these small RNA mediate responses to P deficiency and regulate P homeostasis [11].…”
mentioning
confidence: 99%
“…miRNA156 also targets a variety of mRNAs that encode regulatory proteins involved in various physiological processes in plants ( Wang and Wang, 2015 ). Like miRNA156, miRNA399 was determined to be sucrose-responsive through a microRNA array assay and high levels of sucrose inhibited the accumulation of microRNA399 family under phosphate starvation conditions in Arabidopsis ( Tian et al, 2018b ). miRNA398, that is associated with the adaptive plant response to biotic, abiotic, and nutrient stresses and could be involved in sugar-signaling pathway ( Sunkar et al, 2006 ; Dugas and Bartel, 2008 ; Jia et al, 2009 ; Feng et al, 2015 ).…”
Section: Sugars and Micrornasmentioning
confidence: 99%